2021
DOI: 10.1108/ijem-11-2020-0524
|View full text |Cite
|
Sign up to set email alerts
|

How can universities improve student loyalty? The roles of university social responsibility, service quality, and “customer” satisfaction and trust

Abstract: PurposeStudent loyalty is important if universities are to stay in business by recruiting and retaining satisfied students who provide positive evaluations of their university to others. The current study employed a theoretical framework established by consumer researchers to test the hypothesis that university social responsibility (USR) would predict student loyalty, but that this relation would be mediated by perceived service quality, student satisfaction, and student trust in their university.Design/metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 55 publications
7
70
0
5
Order By: Relevance
“…Different literature on the relationship between customer and service provider has identified trust to be a predictor of customer satisfaction and loyalty (Gul, 2014;Jones & Afnan, 2019) because when a customer is satisfied with service and loyal to the provider, he is basically trusting it (Latif, Bunce, & Ahmad, 2021). Trust is also considered to be a stronger emotion than satisfaction because it better predicts customer loyalty (Ranaweera & Prabhu, 2003;Ismanova, 2019).…”
Section: Trust In University Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Different literature on the relationship between customer and service provider has identified trust to be a predictor of customer satisfaction and loyalty (Gul, 2014;Jones & Afnan, 2019) because when a customer is satisfied with service and loyal to the provider, he is basically trusting it (Latif, Bunce, & Ahmad, 2021). Trust is also considered to be a stronger emotion than satisfaction because it better predicts customer loyalty (Ranaweera & Prabhu, 2003;Ismanova, 2019).…”
Section: Trust In University Settingmentioning
confidence: 99%
“…Specifically, empirical studies have found trust in the university setting to increase collaboration between student and school (Mitchell, Kensler & Tschannen-Moran, 2018;Abdelmaaboud, Peña, & Mahrous, 2020), academic performance (Ennen, Stark & Lassiter, 2015;Latif, Bunce, & Ahmad, 2021), healthy school climates and quality school life (Hongwidjojo, Monika & Wijaya, 2018;Jones & Afnan, 2019), collective teacher efficacy (Flood & Angelle, 2017), triadic set of interactions and academic optimism (Cansoy & Parlar, 2018), and student identification with school (Mitchell, Kensler, & Tschannen-Moran, 2018).…”
Section: Trust In University Settingmentioning
confidence: 99%
“…Section A was designed to solicit demographic profiles of the respondents such as gender, type of students, age, race, and education level. Section B comprised the dimensions of short-form USR, namely ethical and philanthropic responsibilities adapted from (Latif, 2018;Latif et al, 2021). For section B, the researchers used the five-point Likert-type scale with (1) Strongly disagree, (2) Disagree, (3) Somewhat agree, (4) Agree, and (5) Strongly agree to measure the variables.…”
Section: Measurementmentioning
confidence: 99%
“…Hence, the current study focuses on the current students as they are the major stakeholders of the university and universities unable to survive without the students (Dagilienė & Mykolaitienė, 2015;Geryk, 2016). Furthermore, researchers argued that students give more attention to USR practices than other university stakeholders (Kouatli, 2019, Latif et al, 2021, which justified examining students as the institution's main stakeholder. In addition, previous studies have argued that gender plays a significant role when it comes to perceiving the social responsibility practices, where female students will be paying more attention to the social responsibility initiatives as compared to male students (Berényi & Deutsch, 2017;Lu et al, 2020), while other studies found that gender did not influence students' perception on the social responsibility (Teixeira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation